Head and Arm Tremor in X-linked Spinal and Bulbar Muscular Atrophy. (8th October 2014) - Aicua, Irene; Verhagen, Okker; Arenaza, Naroa; Cubo, Esther
Background: X-linked spinal and bulbar muscular atrophy (SBMA) is a rare adult-onset neuronopathy. Although tremor is known to occur in this disease, the number of reported cases of SBMA with tremor is rare, and the number with videotaped documentation is exceedingly rare. Our aim was to describe/document the characteristic signs of tremor in spinal and bulbar muscular atrophy. Case Report: We report a case of a 58-year-old male with a positive family history of tremor. On examination, the patient had jaw and hand tremors but he also exhibited gynecomastia, progressive bulbar paresis, and wasting and weakness primarily in the proximal limb muscles. The laboratory tests revealed an elevated creatine phosphokinase. Genetic testing was positive for X-SBMA, with 42 CAG repeats. Discussion: Essential tremor is one of the most common movement disorders, yet it is important for clinicians to be aware of the presence of other distinguishing features that point to alternative diagnoses. The presence of action tremor associated with muscle atrophy and gynecomastia should lead to a suspicion of SBMA.